Factors that influence the foreign direct investment in Malaysia / Nurul Najihah Abdul Rahman - Abdul Rahman, Nurul Najihah (Faculty of Business and Management, 2018)
This study explores the relationship between foreign direct investment (FDI) and the determinants, market size (MS), exchange rate (ER) and inflation rate (IR) over the period 2009 to 2016. This study has been conducted, Malaysia as reference, using quarterly data in 8 years, starting from 1st 2009 to 4th 2016. The data were collected from Thomsom Reuters Datastream, World Bank and Department of statistic of Malaysia. The empirical analysis of this study was performed by using econometric methods that is Ordinary Least Square (OLS) regression. The findings indicate that there are positive significant relationship between inflation and foreign direct investment. Meanwhile, it was also discovered that there are negative significant relationship between market size and exchange rate towards foreign direct investment. Overall, it was found that inflation rate is the most significant factor influencing foreign direct investment (FDI).